Assessing the influence of local environment, regional climate and tree species on radial growth in the Hexi area of arid northwest China - Fan, Beixi; Yang, Bao; Li, Gang (Frontiers in Plant Science, 2022)
Radial growth is influenced by the local environment, regional climate, and tree species. Assessing the influence of these variables on radial growth can help to reveal the relationships between tree growth and the environment. Here, we reported tree-ring widths (TRW) residual chronologies from five sites along a longitudinal gradient in the Hexi area, arid northwestern China, based on a total of 249 Qinghai spruce (Picea crassifolia) ring-width records. We found that Qinghai spruce in the west of the Hexi area is more sensitive to climate change than in the east, and that drought (scPDSI) in the previous growing season and the early growing season (March to June) limits spruce growth. Comparison between the regional standard chronologies of Qinghai spruce and Qilian juniper (Juniperus przewalskii) in the Hexi area during 1813-2001 showed that both chronologies were more consistent in the high-frequency domain than in the low-frequency domain. The findings emphasize the impacts of local environment, regional climate and tree species on radial growth, suggesting that accounting for these variables could improve large-scale and multi-species dendroclimatic studies.